Aluminum substrate for rechargeable lithium battery, electrode and rechargeable lithium battery

By providing an aluminum substrate with specific microstrain and texture fraction, the problem of damage to the aluminum substrate in the prior art in the rolling process is solved, and a material suitable for the positive electrode current collector of the rechargeable lithium battery is realized, and the processing performance is improved .

CN119447315APending Publication Date: 2025-02-14SAMSUNG SDI CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411048989.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-03
Filing Date
2024-08-01
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the prior art, the aluminum substrate used for the positive electrode current collector of a rechargeable lithium battery is prone to damage in the rolling process, and it is difficult to find a material with suitable microstrain and tensile strength, which affects the processing performance.

Method used

An aluminum substrate is provided that has a microstrain of about 0.04% to 0.11% and a texture fraction of about 60% to 85% (220) plane diffractions according to the laboratory source powder XRD, suitable as a positive for rechargeable lithium batteries. Electrode current collector.

Benefits of technology

The aluminum substrate has excellent physical properties, including high tensile strength and electrochemical safety, and is suitable for positive electrode current collectors in rechargeable lithium batteries, improving processing performance and avoiding material damage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447315A_ABST
    Figure CN119447315A_ABST
Patent Text Reader

Abstract

The present application provides an aluminum substrate for a rechargeable lithium battery current collector, and an electrode and a rechargeable lithium battery including the same, the aluminum substrate having a microstrain of about 0.04% to about 0.11% according to laboratory-derived powder XRD, or having a texture fraction of (220) plane diffraction lines of about 60% to about 85% according to laboratory-derived powder XRD.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Embodiments of the present disclosure provide an aluminum substrate for a rechargeable lithium battery, an electrode including the same, and a rechargeable lithium battery. Background Art

[0002] Portable information devices (such as cellular phones, laptop computers and / or smart phones, etc.) and / or electric vehicles have used rechargeable lithium batteries with high energy density and easy portability as driving power sources. Recently, research has been actively conducted to use rechargeable lithium batteries with high energy density as driving power sources and / or energy storage power sources for hybrid and / or electric vehicles.

[0003] In order to make the electrons transfer uniformly from the positive electrode of the rechargeable lithium battery, a positive electrode current collector is used. Aluminum substrates are widely used as positive electrode current collectors. It is beneficial for these positive electrode current collectors to have high electrochemical stability and conductivity and be commercially available at a low cost. Summary of the invention

[0004] An aluminum substrate having excellent physical properties and suitable for use as a positive electrode current collector for a rechargeable lithium battery is provided.

[0005] In some embodiments, an aluminum substrate for a rechargeable lithium battery current collector is provided, the aluminum substrate having a micro strain of about 0.04% to about 0.11% according to Lab source Powder XRD (X-ray diffraction analysis).

[0006] In some embodiments, an aluminum substrate for a rechargeable lithium battery current collector is provided, the aluminum substrate having a texture fraction of (220) plane diffraction lines of about 60% to about 85% according to laboratory source powder XRD.

[0007] In some embodiments, an electrode for a rechargeable lithium battery is provided, including an aluminum substrate and an electrode active material layer on the aluminum substrate.

[0008] In some embodiments, a rechargeable lithium battery is provided, including: a positive electrode including an aluminum substrate and a positive electrode active material layer on the aluminum substrate; a negative electrode; and an electrolyte.

[0009] In some embodiments, aluminum substrates having suitable or optimal physical properties for use as positive electrode current collectors for rechargeable lithium batteries are provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0010] The accompanying drawings, together with the description, illustrate embodiments of the presently disclosed subject matter, and, together with the description, serve to explain principles of embodiments of the presently disclosed subject matter.

[0011] Figure 1 is a perspective view schematically illustrating a rechargeable lithium battery according to some embodiments.

[0012] Figure 2 is a cross-sectional view schematically illustrating a rechargeable lithium battery according to some embodiments.

[0013] Figure 3 and Figure 4 is a perspective view schematically illustrating a rechargeable lithium battery according to some embodiments.

[0014] Description of Reference Numerals

[0015] 100: Rechargeable lithium battery 10: Positive electrode

[0016] 11: Positive electrode lead lug 12: Positive electrode terminal

[0017] 20: Negative electrode 21: Negative electrode lead lug

[0018] 22: Negative electrode terminal 30: Separator

[0019] 40: electrode assembly 50: shell

[0020] 60: Sealing member 70: Electrode terminal piece

[0021] 71: Positive electrode terminal tab 72: Negative electrode terminal tab DETAILED DESCRIPTION

[0022] Hereinafter, embodiments of the present disclosure will be described in more detail so that those skilled in the art can easily implement them. However, the subject matter of the present disclosure may be embodied in many different forms and should not be construed as limited to the example embodiments set forth herein.

[0023] The terms used herein are only used to describe the embodiments and are not intended to limit the present disclosure. Unless the context clearly dictates otherwise, a singular expression includes a plural expression.

[0024] As used herein, "combinations thereof" means mixtures, laminates, composites, copolymers, alloys, blends, and / or reaction products, etc., of the components being described.

[0025] In this document, it should be understood that terms such as "comprising", "including" or "having" are intended to indicate the presence of embodied features, quantities, steps, elements or combinations thereof, but do not exclude the possibility of the presence or addition of one or more other features, quantities, steps, elements or combinations thereof.

[0026] In the drawings, the thickness of layers, films, panels, regions, etc. may be exaggerated for clarity, and the same reference numerals denote the same elements throughout the specification. It will be understood that if an element (such as a layer, film, region, or substrate) is referred to as being "on" another element, it may be directly on the other element, or intervening elements may also be present. In contrast, if an element is referred to as being "directly on" another element, there are no intervening elements.

[0027] In addition, the term "layer" as used herein includes not only a shape formed on the entire surface if viewed in a plan view but also a shape formed on a partial surface (for example, a part of the surface).

[0028] In addition, the average particle size can be measured by any suitable method commonly used in the art, for example, the average particle size can be measured by a particle size analyzer and / or can be measured by a transmission electron microscope image and / or a scanning electron microscope image. In some embodiments, it is possible to measure by using a dynamic light scattering method, perform data analysis, count the number of particles in each particle size range, and calculate the average particle size value. Unless otherwise specified, the average particle size (D 50 ) may refer to the diameter of particles having a cumulative volume of 50% by volume in a particle size distribution. As used herein, if no definition is provided otherwise, the average particle size (D 50 ) means the diameter of a particle having a cumulative volume of 50 volume % in a particle size distribution obtained by randomly measuring the size (diameter or length of the major axis) of about 20 particles in a scanning electron microscope image.

[0029] In this document, "or" is not interpreted as an exclusive meaning. For example, "A or B" is interpreted as including A, B and / or A+B, etc.

[0030] The term "metal" as used herein is interpreted as a concept including ordinary metals, transition metals, and metalloids (semimetals).

[0031] Aluminum substrate

[0032] The aluminum substrate for a rechargeable lithium battery current collector according to some embodiments satisfies a microstrain of about 0.04% to about 0.11% according to a laboratory source powder XRD. The embodiments of the aluminum substrate have excellent physical properties (such as tensile strength, elongation, electrochemical safety, and electronic conductivity (e.g., conductivity)), making it suitable or optimized for application as a positive electrode current collector for a rechargeable lithium battery.

[0033] The result values ​​of the physical properties of the aluminum substrate, such as tensile strength, have relatively high fluctuations depending on the measurement environment, but the microstrain has little change depending on the measurement environment, so that the consistency of the results is high. In addition, the microstrain can be easily measured using a general laboratory source powder XRD. Laboratory source powder XRD may refer to powder X-ray diffraction using a laboratory source (e.g., a Cu-Kα1 source), and the measuring device may be, for example, a D8 Advance manufactured by Bruker. It was found that microstrain has a very high positive correlation with tensile strength, and accordingly, it is believed that it can replace tensile strength evaluation. It was confirmed that the correlation coefficient between microstrain and tensile strength exceeded approximately 90%.

[0034] The term microstrain refers to the slight inhomogeneity and / or deformation within the crystal lattice of a metal. If stress is applied to a metal material, such as during cold working, microstrain may be generated. In some embodiments, microstrain may occur if a solid solution is formed due to foreign elements within the metal. The microstrain may be calculated using the diffusion phenomenon of XRD diffraction lines and may be calculated using the following equation 1.

[0035] Equation 1

[0036] FWHM×cosθ=ε×4sinθ

[0037] In Equation 1, FWHM is the full width at half maximum and ε is the microstrain value.

[0038] For example, the aluminum substrate according to some embodiments may have a face-centered cubic (FCC) structure, and thus may be preferably oriented to the (220) plane and the (311) plane. The angle of the (220) plane may be 64° to 66°, and the angle of the (311) plane may be 77° to 79°. The angle of each crystal plane, the Bragg angle corresponding to the origin, and the half-peak full width on each crystal plane are entered into Equation 1 to calculate ε.

[0039] Microstrain can be measured using, for example, the Williamson-Hall method (WH method), wherein for further information on microstrain and its calculation method, see "ACTA METALLURGICA, VOL. 1, JAN. 1953. 22-31, GK Williamson and WH Hall, X-RAY LINE BROADENING FROM FILED ALUMINIUM AND WOLFRAM" or "Ron Jenkins, Robert L. Snyder, Introduction to X-ray Powder Diffractometry, Vol. 138, p. 93, 1996", the contents of which related to microstrain are incorporated herein by reference.

[0040] The microstrain according to some embodiments may be in a range of about 0.04% to about 0.11%, for example, about 0.05% to about 0.10%, or about 0.06% to about 0.09%.

[0041] The aluminum substrate may have a face-centered cubic structure, which is Fm-3m of space group No. 225. The aluminum substrate may be said to have 3 aluminum atoms at 6 face centers (1 / 2×6) and 1 aluminum atom at 8 vertices (1 / 8×8) in a unit cell. The unit cell has approximately The length of the unit cell.

[0042] The aluminum substrate for a rechargeable lithium battery current collector according to some embodiments may have a texture fraction of (220) plane diffraction lines in the range of about 60% to about 85% according to laboratory source powder XRD. Such an aluminum substrate may exhibit suitable or optimal characteristics as a positive electrode current collector for a rechargeable lithium battery.

[0043] The texture fraction is obtained by converting the texture coefficient (TC) of each crystal plane into a percentage in the face-centered cubic structure of the aluminum substrate, and can be expressed as the (220) plane texture fraction of the aluminum substrate, "the fraction of TC of Fm-3m Al 220", etc. The texture fraction can be referred to as the ND (normal direction) texture fraction of the aluminum substrate. ND is the direction perpendicular to the surface of the aluminum substrate, and is also perpendicular to the RD (rolling direction) and TD (transverse direction). For texture fractions, see International Crystallography Association of Al (PDF 04-0787), "Isao YAGI et. Al., Journal of the Ceramic Society of Japan, 102 3, p. 297 (1994)" or "CS Barret and TBMassalski, Structure of Metals, Pergamon Press, Oxford, p. 204 (1980)", which are incorporated herein by reference for content related to texture fractions. For example, TC can be calculated using Equation 2.

[0044] Equation 2

[0045]

[0046] In Equation 2, I(hkl) and I0(hkl) indicate the integrated intensity of (hkl) diffraction of the experimental sample and the standard powder sample, respectively, n is the total number of diffraction planes, and Σ is their sum. The TC of the (220) plane is the value obtained by inputting the (220) plane into the (hlk) plane of Equation 2.

[0047] The aluminum substrate according to some embodiments may have a (220) plane texture fraction of about 60% to about 85%, for example, about 62% to about 84%.

[0048] The aluminum substrate according to some embodiments may have a relative humidity of about 2.69 g / cm according to laboratory source powder XRD. 3 ~about 2.71g / cm 3 The X-ray density can be obtained by dividing the weight of the elements in the unit lattice (unit cell) by the volume of the unit lattice. For X-ray density and its measurement method, see "BD Cullity, Addison-Wesley Pub. Co. Inc., 1978, pp. 88 to pp. 89", wherein the content related to X-ray density and its measurement is incorporated herein by reference.

[0049] For example, X-ray density can be calculated using Equation 3.

[0050] Equation 3

[0051]

[0052] In Equation 3, ρ indicates the X-ray density (g / cm 3 ), ΣA is the sum of the atomic weights of all elements in the unit lattice, N is Avogadro's number, and V is the volume of the unit lattice in cm 3 , V' is the volume of the unit cell, in units of

[0053] For example, an aluminum substrate may have a thickness of about 2.699 g / cm 3 ~about 2.706g / cm 3 The X-ray density.

[0054] In some embodiments, the aluminum substrate may have a thickness of less than or equal to about 20 μm, for example, about 9 μm to about 15 μm, or about 10 μm to about 15 μm, for example, about 10 μm, about 13.5 μm, or about 15 μm.

[0055] In some embodiments, the aluminum substrate may have a strength of about 80 N / mm 2 ~About 320N / mm 2 , for example, about 100 N / mm 2 ~About 320N / mm 2 , about 150N / mm 2 ~About 320N / mm 2 , or about 200N / mm 2 ~About 320N / mm 2UTM (Universal Testing Machine) tensile strength.

[0056] The aluminum substrate satisfying the aforementioned characteristics can be manufactured by adjusting the type (or kind) of the original metal material, the temperature and / or pressure conditions in the thin film process and / or the drying process, the presence or absence of the forming process and / or its conditions, the presence or absence of the additional pressing process and / or its method, etc. The characteristics of the aluminum substrate can be determined by the conditions of the casting, annealing and / or rolling process. The final characteristics may be different according to the content of each chemical component including the alloy in the casting process, and can also be adjusted by conditions such as heat treatment temperature, time, etc. in the annealing process. The rolling process can be divided into hot rolling and cold rolling, and the characteristics of the final substrate such as strength, etc. can be changed according to the thickness and pressing rate of the material input into each process.

[0057] The method of manufacturing the aluminum substrate may include continuous casting and / or direct casting, etc. Continuous casting may include, for example, dissolving raw materials, casting, annealing, cold rolling and / or cutting. Direct casting may include, for example, dissolving raw materials, casting, faceting, homogenizing, hot rolling, cold rolling, annealing and / or cutting.

[0058] Rechargeable lithium battery

[0059] In some embodiments, an electrode for a rechargeable lithium battery includes an aluminum substrate and an electrode active material layer on the aluminum substrate.

[0060] For example, the electrode may be a positive electrode. Accordingly, some embodiments provide a positive electrode for a rechargeable lithium battery, the positive electrode comprising an aluminum substrate as a positive electrode current collector and a positive electrode active material layer on the aluminum substrate.

[0061] In some embodiments, a rechargeable lithium battery includes: a positive electrode including an aluminum substrate and a positive electrode active material layer on the aluminum substrate; a negative electrode; and an electrolyte. Herein, the electrolyte may be a liquid electrolyte (ie, an electrolyte solution) or a solid electrolyte.

[0062] For example, in some embodiments, a rechargeable lithium battery may include: a positive electrode including the aforementioned aluminum substrate and a positive electrode active material layer; a negative electrode; a separator between the positive electrode and the negative electrode; and an electrolyte solution. As another example, an all-solid-state rechargeable lithium battery may include: a positive electrode including the aforementioned aluminum substrate and a positive electrode active material layer; a negative electrode; and a solid electrolyte layer between the positive electrode and the negative electrode.

[0063] Hereinafter, a rechargeable lithium battery using an electrolyte solution will be described as an example, but the present disclosure is not limited thereto.

[0064] Rechargeable lithium batteries may be classified into a cylindrical shape, a prismatic shape, a pouch shape, a coin shape, etc. according to their shapes. Figure 1is a perspective view schematically illustrating a rechargeable lithium battery according to some embodiments. Figure 2 is a cross-sectional view schematically illustrating a rechargeable lithium battery according to some embodiments. Figure 3 and Figure 4 is a perspective view schematically illustrating a rechargeable lithium battery according to some embodiments. Figure 1 A cylindrical battery is shown, Figure 2 A prismatic cell is shown, Figure 3 and Figure 4 Pouch cell shown. Figure 1 to Figure 4 , the rechargeable lithium battery 100 includes: an electrode assembly 40, a separator 30 including a positive electrode 10 and a negative electrode 20; and a case 50 including the electrode assembly 40. The positive electrode 10, the negative electrode 20 and the separator 30 may be impregnated with an electrolyte solution. Figure 1 As shown in , the rechargeable lithium battery 100 may include a sealing member 60 that seals the housing 50. Figure 2 In the embodiment, the rechargeable lithium battery 100 may include a positive electrode lead tab 11, a positive electrode terminal 12, a negative electrode lead tab 21, and a negative electrode terminal 22. Figure 3 and Figure 4 As shown in FIG. 1 , the rechargeable lithium battery 100 includes an electrode tab 70 ( Figure 4 ), for example, the positive electrode terminal tab 71 and the negative electrode terminal tab 72 ( Figure 3 ) serves as an electrical path for inducing the current formed in the electrode assembly 40 to the outside.

[0065] Positive electrode

[0066] The positive electrode for a rechargeable lithium battery may include the aforementioned aluminum substrate as a positive electrode current collector and a positive electrode active material layer on the aluminum substrate. The positive electrode active material layer includes a positive electrode active material and may further include a binder and / or a conductive material (eg, an electrically conductive material).

[0067] The positive electrode active material may include a compound capable of intercalating and deintercalating lithium (lithiated intercalation compound). For example, at least one of a composite oxide of lithium and a metal selected from cobalt, manganese, nickel, and a combination thereof may be used.

[0068] The composite oxide may be a lithium transition metal composite oxide, and examples thereof may include lithium nickel-based oxides, lithium cobalt-based oxides, lithium manganese-based oxides, lithium iron phosphate-based compounds, cobalt-free lithium nickel manganese-based oxides, or combinations thereof.

[0069] As an example, a compound represented by any one of the following chemical formulas may be used. a A 1-b X b O 2-c Dc (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05);Li a Mn 2-b X b About 4-c D c (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05);Li a Ni 1-b-c Co b X c About 2-α D α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni 1-b - c Mn b X c About 2-α D α (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.5,0<α<2);Li a Ni b Co c L 1 d G e O2(0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0≤d≤0.5,0≤e≤0.1);Li a NiG b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a CoG b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a Mn 1-b G b O2(0.90≤a≤1.8,0.001≤b≤0.1);Li a Mn2G b O4(0.90≤a≤1.8,0.001≤b≤0.1);Li a Mn 1-g G g PO4(0.90≤a≤1.8,0≤g≤0.5);Li (3-f) Fe2(PO4)3(0≤f≤2);Li a FePO4(0.90≤a≤1.8).

[0070] In the above chemical formula, A is Ni, Co, Mn or a combination thereof; X is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element or a combination thereof; D is O, F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; and L 1 It is Mn, Al or a combination thereof.

[0071] For example, the positive electrode active material may be a high nickel positive electrode active material having a nickel content of greater than or equal to about 80 mol%, greater than or equal to about 85 mol%, greater than or equal to about 90 mol%, greater than or equal to about 91 mol% or greater than or equal to about 94 mol% and less than or equal to about 99 mol%, based on 100 mol% of metals other than lithium in the lithium transition metal composite oxide. The high nickel positive electrode active material can achieve high capacity and can be applied to high capacity, high density rechargeable lithium batteries.

[0072] The amount of the positive electrode active material may be about 90 wt % to about 99.5 wt % based on 100 wt % of the positive electrode active material layer, and the amount of the binder and the conductive material may be about 0.5 wt % to about 5 wt % based on 100 wt % of the positive electrode active material layer, respectively.

[0073] The binder improves the bonding properties of the positive electrode active material particles to each other and to the positive electrode current collector. Examples of the binder may include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylic resin, polyester resin, and nylon, but are not limited thereto.

[0074] The conductive material is included to provide electrode conductivity (e.g., electrical conductivity), and any suitable conductive material may be used as the conductive material unless it causes chemical changes (e.g., undesirable chemical changes in a rechargeable lithium battery). Examples of the conductive material may include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube, etc.; metal-based materials including metal powders and / or metal fibers of copper, nickel, aluminum, and / or silver, etc.; conductive polymers (e.g., conductive polymers) such as polyphenylene derivatives; and / or mixtures thereof.

[0075] Negative electrode

[0076] The negative electrode for a rechargeable lithium battery includes a negative electrode current collector and a negative electrode active material layer on the negative electrode current collector. The negative electrode active material layer may include a negative electrode active material, and may further include a binder and / or a conductive material (e.g., a conductive material).

[0077] The negative electrode active material may include a material that reversibly intercalates / deintercalates lithium ions, lithium metal, a lithium metal alloy, a material capable of doping / dedoping lithium, and / or a transition metal oxide.

[0078] The material that reversibly intercalates / deintercalates lithium ions may include, for example, crystalline carbon, amorphous carbon, or a combination thereof as a carbon-based negative electrode active material. The crystalline carbon may be irregular and / or flaky, sheet-like, spherical, and / or fibrous natural graphite and / or artificial graphite. The amorphous carbon may be soft carbon, hard carbon, a mesophase pitch carbonized product, and / or calcined coke, etc.

[0079] The lithium metal alloy includes an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.

[0080] The material capable of doping / dedoping lithium may be a Si-based negative electrode active material and / or a Sn-based negative electrode active material. The Si-based negative electrode active material may include silicon, a silicon-carbon composite, SiO x (0 < x < 2), a Si-Q alloy (where Q is selected from alkali metals, alkaline earth metals, group 13 elements, group 14 elements (excluding Si), group 15 elements, group 16 elements, transition metals, rare earth elements, and combinations thereof), or a combination thereof. The Sn-based negative electrode active material may be Sn, SnO2, a Sn-based alloy, or a combination thereof.

[0081] The silicon-carbon composite may be a composite of silicon and amorphous carbon. According to some embodiments, the silicon-carbon composite may be in the form of silicon particles and an amorphous carbon coating on the surface of the silicon particles. For example, it may include secondary particles (cores) in which silicon primary particles are aggregated and an amorphous carbon coating (shells) on the surface of the secondary particles. The amorphous carbon may also be present between the silicon primary particles. For example, the silicon primary particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.

[0082] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include a core containing crystalline carbon and silicon particles and an amorphous carbon coating on the surface of the core.

[0083] The Si-based negative electrode active material and / or the Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material.

[0084] For example, the negative electrode active material layer may include about 90 wt % to about 99 wt % of the negative electrode active material, about 0.5 wt % to about 5 wt % of the binder, and about 0 wt % to about 5 wt % of the conductive material.

[0085] The binder is used to bind the negative electrode active material particles well to each other and also to bind the negative electrode active material to the negative electrode current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder or a combination thereof.

[0086] The non-aqueous binder may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamideimide, polyimide, or a combination thereof.

[0087] The aqueous binder may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinyl pyrrolidone, polyepichlorohydrin, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinyl pyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenol resin, epoxy resin, polyvinyl alcohol or a combination thereof.

[0088] If the aqueous binder is used as the negative electrode binder, a cellulose compound capable of imparting or increasing viscosity may be further included. As the cellulose compound, one or more selected from carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose and alkali metal salts thereof may be mixed and used. The alkali metal may be Na, K and / or Li.

[0089] The dry binder may be a polymer material that can be turned into fibers, and may be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or a combination thereof.

[0090] The conductive material is included to provide electrode conductivity (e.g., electrical conductivity), and any suitable conductive material can be used as the conductive material unless it causes chemical changes (e.g., undesirable chemical changes in a rechargeable lithium battery). Examples of the conductive material include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, carbon nanofiber, and carbon nanotube, etc.; metal-based materials including metal powders and / or metal fibers of copper, nickel, aluminum, and / or silver, etc.; conductive polymers (e.g., conductive polymers) such as polyphenylene derivatives; and / or mixtures thereof.

[0091] The negative electrode current collector may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal (eg, an electrically conductive material), and combinations thereof.

[0092] Electrolyte solution

[0093] The electrolyte solution for a rechargeable lithium battery includes a non-aqueous organic solvent and a lithium salt.

[0094] The nonaqueous organic solvent serves as a medium for transporting ions participating in the electrochemical reaction of the battery.

[0095] The non-aqueous organic solvent may be a carbonate solvent, an ester solvent, an ether solvent, a ketone solvent, an alcohol solvent, an aprotic solvent or a combination thereof.

[0096] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), ethyl methyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC) and / or butylene carbonate (BC), etc. Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, dimethyl acetate, methyl propionate, ethyl propionate, decanoic acid lactone, mevalonate lactone, valerolactone and / or caprolactone, etc. Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran and / or tetrahydrofuran, etc. In some embodiments, ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol and / or isopropanol, etc., and aprotic solvents may include nitriles (such as R-CN, where R is a C2-C20 straight chain, branched or cyclic hydrocarbon group, including double bonds, aromatic rings and / or ether bonds, etc.); amides (such as dimethylformamide); dioxolanes (such as 1,3-dioxolane and / or 1,4-dioxolane, etc.); and / or sulfolane, etc.

[0097] The nonaqueous organic solvent may be used alone or in mixture of two or more types (or species).

[0098] In some embodiments, if a carbonate-based solvent is used, a cyclic carbonate and a chain carbonate may be mixed together and used, and the cyclic carbonate and the chain carbonate may be mixed together in a volume ratio of about 1:1 to about 1:9.

[0099] The lithium salt dissolved in the non-aqueous organic solvent supplies lithium ions in the battery, enables the basic operation of the rechargeable lithium battery, and improves the transport of lithium ions between the positive electrode and the negative electrode. Examples of lithium salts may include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO3C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F2x+1 SO2)(C y F 2y+1 SO2) (x and y are integers of 1 to 20), at least one of lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalato)phosphate (LiDFOB) and lithium bis(oxalato)borate (LiBOB).

[0100] Diaphragm

[0101] Depending on the type (or kind) of the rechargeable lithium battery, there may be a separator between the positive electrode and the negative electrode. The separator may include polyethylene, polypropylene, polyvinylidene fluoride, or a multilayer film of two or more layers thereof, and a mixed multilayer film (such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, and / or a polypropylene / polyethylene / polypropylene three-layer separator, etc.).

[0102] The separator may include a porous substrate and a coating including an organic material, an inorganic material, or a combination thereof on one or both surfaces of the porous substrate.

[0103] The porous substrate may be a polymer film formed by any one selected from the group consisting of polymer polyolefins (such as polyethylene and polypropylene), polyesters (such as polyethylene terephthalate and polybutylene terephthalate), polyacetals, polyamides, polyimides, polycarbonates, polyetherketones, polyaryletherketones, polyetheretherketones, polyetherimides, polyamideimides, polybenzimidazoles, polyethersulfones, polyphenylene oxides, cyclic olefin copolymers, polyphenylene sulfide, polyethylene naphthalate, glass fibers, TEFLON, and polytetrafluoroethylene, or a polymer film formed by a copolymer or a mixture of two or more thereof.

[0104] The organic material may include a polyvinylidene fluoride-based polymer and / or a (meth)acrylic-based polymer.

[0105] The inorganic material may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, GaO, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite and combinations thereof, but is not limited thereto.

[0106] The organic material and the inorganic material may be mixed together in one coating layer, or a coating layer including an organic material and a coating layer including an inorganic material may be stacked.

[0107] Examples and Comparative Examples

[0108] The following describes embodiments and comparative examples of the present disclosure. However, the embodiments described below are merely examples of the present disclosure, and the present disclosure is not limited to the embodiments described below.

[0109] In Table 1, the laboratory source powder XRD information and UTM tensile strength of the aluminum substrates according to Examples 1 to 9 are shown respectively. In Table 1, A1100 and A8021 represent aluminum types. The term "ambient" refers to the drying temperature, and IHA of Example 9 means induction heat annealing, which refers to a process of reducing the tensile strength of an Al rolled substrate by self-induction heating. IHA7.0kW indicates that a self-induction heating annealing process is performed using an electrical power of 7.0kW. In Examples 6 and 7, VD refers to vacuum drying, and VD@120°C indicates that vacuum drying is performed at 120°C. The term "forming" in Example 8 means performing a forming process.

[0110] (Table 1)

[0111]

[0112]

[0113] In Table 1, laboratory-derived powder XRD was performed by using powder XRD (D8 Advance) manufactured by Bruker under the following conditions.

[0114] -X-ray wavelength: (CuKα1)

[0115] - Slit conditions: divergence slit 0.5°, scattering slit 0.5°, receiving slit 0.20mm

[0116] - Scanning conditions: continuous scanning, 35°≤2θ≤120°, 0.01° / step, 2.84° / min, total measurement time 30 min.

[0117] - Sample stage rotation speed: 10rpm

[0118] The methods for measuring microstrain, (220) plane texture fraction and X-ray density are the same as above.

[0119] The UTM tensile strength was measured by using a tensile strength tester of UTM3342 (universal testing machine) manufactured by Instron.

[0120] In the process of manufacturing a positive electrode for a rechargeable lithium battery cell, the positive electrode is rolled to densify the positive electrode active material layer and increase the bonding force between the aluminum substrate of the thin film current collector and the positive electrode active material layer. However, the aluminum substrate of the thin film current collector is damaged due to the high pressure in the rolling process. Accordingly, an aluminum substrate with high strain characteristics and high tensile strength is desired or preferred, but if the microstrain is too high, the aluminum substrate may bend, thereby deteriorating the processing performance. In order to improve the bending phenomenon, there may be a method of performing induction thermal annealing (IHA) before rolling the positive electrode to reduce the microstrain and thus increase the processing performance, but if the microstrain becomes too low, the aluminum substrate may adhere to the IHA serrations or tear. Accordingly, it is important to manufacture the aluminum substrate as a film having microstrain characteristics within a suitable or appropriate range.

[0121] For example, the aluminum substrate of Comparative Example 1, which was heat treated at 200°C for 12 hours, exhibited a microstrain of about 0.034%, but had a low tensile strength, which proved to be unsuitable as a positive electrode current collector. The A3104 aluminum substrate of Comparative Example 2 exhibited a microstrain of about 0.156% and a tensile strength of 355 N / mm 2 The A1100 aluminum substrate of Comparative Example 3, which was heat treated at 140°C for 1 hour, showed a (220) surface texture fraction of 59%, but had low tensile strength, and was not suitable as a positive electrode current collector.

[0122] In contrast, referring to Table 1, Examples 1 to 9 each exhibit microstrain satisfying the range of 0.04% to 0.11%, (220) plane texture fraction of 60% to 85%, and a microstructure of 2.69 g / cm 3 ~2.71g / cm 3 The aluminum substrate of the embodiment has suitably high tensile strength and thus is not damaged during a positive electrode manufacturing process or a battery manufacturing process, and does not exhibit a bending phenomenon to ensure excellent processing properties, and as a result, it turns out to be most suitable as a positive electrode current collector for a rechargeable lithium battery.

[0123] Although the subject matter of the present disclosure has been described in conjunction with what are presently considered to be practical example embodiments, it is to be understood that the present disclosure is not limited to the disclosed embodiments, but is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the claims and their equivalents.

Claims

1. An aluminum substrate for a rechargeable lithium battery current collector, the aluminum substrate having a microstrain of 0.04% to 0.11% according to laboratory source powder XRD.

2. The aluminum substrate according to claim 1, wherein: The thickness of the aluminum substrate is less than or equal to 20 μm.

3. The aluminum substrate according to claim 1, wherein: The thickness of the aluminum substrate is 9 μm to 15 μm.

4. The aluminum substrate according to claim 1, wherein: The tensile strength of the aluminum substrate is 80N / mm 2 ~320N / mm 2 .

5. The aluminum substrate according to claim 1, wherein: The X-ray density of the powder XRD from the laboratory source is 2.69 g / cm 3 ~2.71g / cm 3 .

6. An aluminum substrate for a current collector of a rechargeable lithium battery, the aluminum substrate having a texture fraction of (220) plane diffraction lines of 60% to 85% according to laboratory source powder XRD.

7. The aluminum substrate according to claim 6, wherein: The thickness of the aluminum substrate is less than or equal to 20 μm.

8. The aluminum substrate according to claim 6, wherein: The thickness of the aluminum substrate is 9 μm to 15 μm.

9. The aluminum substrate according to claim 6, wherein: The tensile strength of the aluminum substrate is 80N / mm 2 ~320N / mm 2 .

10. The aluminum substrate according to claim 6, wherein: The X-ray density of the powder XRD from the laboratory source is 2.69 g / cm 3 ~2.71g / cm 3 . 11 . An electrode for a rechargeable lithium battery, comprising the aluminum substrate according to claim 1 and an electrode active material layer on the aluminum substrate.

12. A rechargeable lithium battery comprising: A positive electrode, comprising an aluminum substrate as claimed in any one of claims 1 to 10 and an electrode active material layer on the aluminum substrate; Negative electrode; as well as Electrolytes.